The conceptual framework of concreteness in learning representations : a systematic review of theoretical and empirical research utilizing concrete and abstract representations for concreteness fading - Huang, Xiaoshan (My University, 2020)
Issues in the inconsistent learning and transfer performances resulting from the concreteness fading are raises to understand and develop this instructional technique further. Concreteness fading requires the well-articulated sequence of the concrete representation to abstract representation to support learners' conceptual understanding and construction of generic transferrable knowledge. Various research has recently argued the problematic issues in designing appropriate concrete representation based on the existing framework of concreteness and abstraction. The current research conducted qualitative research with thematic analysis, systematically reviewing the theoretical and empirical research, to propose a comprehensive framework of concreteness in three dimensions, objectivity (OB), familiarity (FA), and relevancy (RE). The current research developed a conceptual framework of three-dimensions concreteness as a guideline for understanding and operationalizing the concrete representation to support concreteness fading, which connects the abstract knowledge in learning representation with the external physical world, learners' knowledge system, and learning objectives. Current research recommends the design of concrete representation should include all three dimensions of concreteness to support concreteness fading. Further empirical research is needed to examine the effectiveness of the three-dimensional concrete representation in learners’ learning and transfer performance.